Analisis Yuridis Terhadap Pandemi Covid-19 Sebagai Kategori Overmacht dalam Melakukan Restrukturisasi Perjanjian Kredit - Hamsu Abdul Gani; Andika Wahyudi Gani (Seminar Nasional LP2M UNM, 2021)
Abstract. The results of the research on the juridical analysis of the Covid-19 pandemic as an overmacht category in restructuring credit agreements, it can be concluded that when viewed from the criteria for coercive circumstances, the criteria for Covid-19 are included in the category of relative coercive circumstances, namely situations where it is still possible to carry out and fulfill achievement, with several dispensation methods including the method of renegotiating the agreement in this case in the form of restructuring. As it has been determined that Covid-19 is included in the relative overmacht category, debtors are expected to continue to fulfill their achievements to creditors. Therefore, efforts to mitigate non-performing loans using the restructuring method, as referred to the Financial Services Authority Regulation No. 11 of 2020.Keywords: Covid-19, Overmacht, Restructuring